2019
DOI: 10.1007/s40279-019-01191-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Intervention on Health-Related Physical Fitness and Blood Pressure in Preschool Children: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Effects of exercise intervention on health-related physical fitness and blood pressure in preschool children: A systematic review and meta-analysis of randomized controlled trials

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
32
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 61 publications
7
32
0
3
Order By: Relevance
“…Health-related physical fitness comprises cardiorespiratory fitness, i.e., the ability to perform with the whole body for a prolonged period; flexibility, or the range of motion of a joint or group of joints; muscular strength, which indicates the maximum amount of force that a muscle can exert against any resistance on a short time; and muscular endurance, describing the ability of a muscle to sustain several contractions over a prolonged time [4]. Evidence of the value of physical fitness for youth's health is shown in several studies associating it with, among others, better cardiovascular function [5], movement skills [6], or weight status and obesity [7,8]. Regarding the psychological domain of health, psychological wellbeing is defined as the combination of positive effects and optimal social and personal efficiency [9]; self-esteem represents confidence in and respect of oneself; anxiety is characterized by a feeling of unease about situations with uncertain outcome; while stress is a psychophysical response when facing demanding or adverse environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Health-related physical fitness comprises cardiorespiratory fitness, i.e., the ability to perform with the whole body for a prolonged period; flexibility, or the range of motion of a joint or group of joints; muscular strength, which indicates the maximum amount of force that a muscle can exert against any resistance on a short time; and muscular endurance, describing the ability of a muscle to sustain several contractions over a prolonged time [4]. Evidence of the value of physical fitness for youth's health is shown in several studies associating it with, among others, better cardiovascular function [5], movement skills [6], or weight status and obesity [7,8]. Regarding the psychological domain of health, psychological wellbeing is defined as the combination of positive effects and optimal social and personal efficiency [9]; self-esteem represents confidence in and respect of oneself; anxiety is characterized by a feeling of unease about situations with uncertain outcome; while stress is a psychophysical response when facing demanding or adverse environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Physical fitness also has a positive effect on a wide range of psychological indicators (depression, cognition, social and sports competence, and self-esteem) [ 3 ]. Moreover, preschool children who regularly participate in physical activity have long-term benefits for physical and psychological well-being [ 4 ]. Therefore, the consistent monitoring of the level of physical fitness of individuals should be a priority for public health [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the consistent monitoring of the level of physical fitness of individuals should be a priority for public health [ 5 ]. Accordingly, exercise programs with the aim of improving physical fitness in children and, consequently, improving their health are needed [ 4 ]. Unfortunately, there are limited data on preschool-aged children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that being physically active and having higher levels of cardiorespiratory fitness benefit health, functional ability, quality of life, and longevity [16,17]. Furthermore, a recent metaanalysis showed that children who participated in exercise interventions presented significant reductions in BMI, waist circumference, and %FM as well as increases in cardiorespiratory fitness, lower-body strength, and speed-agility compared to controls [18]. Additionally, adolescents who are physically active present higher levels of cardiovascular fitness, a better blood lipid profile, and lower body adiposity [16].…”
Section: Introductionmentioning
confidence: 99%